2018
DOI: 10.1093/gerona/gly012
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Products of 5-Methylcytosine are Decreased in Senescent Cells and Tissues of Progeroid Mice

Abstract: 5-Hydroxymethylcytosine and 5-formylcytosine are stable DNA base modifications generated from 5-methylcytosine by the ten-eleven translocation protein family that function as epigenetic markers. 5-Hydroxymethyluracil may also be generated from thymine by ten-eleven translocation enzymes. Here, we asked if these epigenetic changes accumulate in senescent cells, since they are thought to be inversely correlated with proliferation. Testing this in ERCC1-XPF-deficient cells and mice also enabled discovery if these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…However, when the data obtained from embryonic axes subjected to accelerated ageing were analyzed, concomitant increases in ROS and 8-oxoG were clearly evident, while no such increase in hm 5 C was observed in embryonic axes subjected to accelerated aging. This is contrary to what one would expect for oxidative DNA damage resulting from increased levels of ROS ( Figure 2 ), however it is in concordance with previous studies, as it has been reported that there is no correlation between the age of adult mice and the level of hm 5 C in Purkinje and granule cells [ 32 ], while a decrease in hm 5 C was recently reported in mouse cells and tissues subjected to physiological and accelerate aging [ 74 ]. Therefore, it could be hypothesized that the level of hm 5 C can be affected by the accumulation of its oxidized forms (fo 5 C and ca 5 C), which have been detected in plant genomes [ 7 ].…”
Section: Discussionsupporting
confidence: 83%
“…However, when the data obtained from embryonic axes subjected to accelerated ageing were analyzed, concomitant increases in ROS and 8-oxoG were clearly evident, while no such increase in hm 5 C was observed in embryonic axes subjected to accelerated aging. This is contrary to what one would expect for oxidative DNA damage resulting from increased levels of ROS ( Figure 2 ), however it is in concordance with previous studies, as it has been reported that there is no correlation between the age of adult mice and the level of hm 5 C in Purkinje and granule cells [ 32 ], while a decrease in hm 5 C was recently reported in mouse cells and tissues subjected to physiological and accelerate aging [ 74 ]. Therefore, it could be hypothesized that the level of hm 5 C can be affected by the accumulation of its oxidized forms (fo 5 C and ca 5 C), which have been detected in plant genomes [ 7 ].…”
Section: Discussionsupporting
confidence: 83%
“…The fact that the signal intensity for the m/z of 242→126 5-MdC modification is several orders-of-magnitude higher than other putative adducts in all tissues ( Fig. 1, Supplementary Table 1 ) is consistent with its presence as ∼1% of all dC in the human genome 16, 17 . Also consistent with the quantitative rigor of the method, we detected an age-dependent signal with m/z 326→210 at much lower levels than 5-MdC and identified it as N 2 -carboxymethyl-2’-deoxyguanosine ( N 2 -CMdG) ( Fig.…”
Section: Main Textsupporting
confidence: 71%
“…To validate the adductomic results, we performed sensitive and specific absolute quantification of these adducts, using isotope dilution triple-quadrupole mass spectrometry, as shown in Figure 4, Extended Data Figure 6, and Supplementary Table 3. The epigenetic mark 5-HMdC was previously observed to increase with age in mouse liver, kidney and brain 16,17 and in human tissues 19 . Our study confirmed this increase in rats aged 1 to 26 months in liver (2.8-fold, Fig.…”
Section: Adductome Analysis In Rat Tissues Reveals Age-dependent Dna ...mentioning
confidence: 89%
See 1 more Smart Citation
“…By giving consideration to the above, various mechanisms together, we are building a better picture of how ‘damage’, or perhaps more accurately ‘modifications’, are involved in the disease process. This is leading to a better understanding of how oxidative stress, DNA damage/genomic instability, gene regulatory mechanisms and DNA repair, can influence the cellular redox status, maintain homeostasis, or contribute to, or prevent, the development or progression of various diseases (discussed in Mikhed et al [ 27 ], and Gorinin et al [ 28 ]), which include cancer [ 29 , 30 ], Alzheimer's disease [ 31 ], and other neurodegenerative diseases [ 32 ], and also ageing [ 33 , 34 ].…”
Section: Formation Repair and Consequences Of Damage To Nucleic Acidsmentioning
confidence: 99%